2007
DOI: 10.1016/s1474-4422(07)70220-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological effects of high-dose idebenone in patients with Friedreich's ataxia: a randomised, placebo-controlled trial

Abstract: SummaryBackground Friedreich's ataxia (FA) is a progressive, multisystem, degenerative disorder caused by a reduction in frataxin. Loss of frataxin results in mitochondrial dysfunction and oxidative damage in patients and model systems. Previous studies have indicated that the antioxidant idebenone (5 mg/kg daily) reduces cardiac hypertrophy, but defi nite improvement in neurological function has not been shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(172 citation statements)
references
References 22 publications
(40 reference statements)
6
161
2
2
Order By: Relevance
“…The link between iron misregulation and oxidative damage is similar to current evidence regarding the pathogenesis of Friedreich's ataxia in which loss of frataxin impairs mitochondrial iron handling resulting in increased oxidative stress and cellular damage [21]. In the case of Friedreich's ataxia, clinical trials have shown benefit with antioxidant therapy such as idebenone [22,23], with clinical benefits particularly apparent in children and younger patients. This demonstrates the importance of early treatment instigation in these patients [23] and, in conjunction with the findings of this study, supports the case for early intervention in patients with neuroferritinopathy.…”
Section: Discussionsupporting
confidence: 62%
“…The link between iron misregulation and oxidative damage is similar to current evidence regarding the pathogenesis of Friedreich's ataxia in which loss of frataxin impairs mitochondrial iron handling resulting in increased oxidative stress and cellular damage [21]. In the case of Friedreich's ataxia, clinical trials have shown benefit with antioxidant therapy such as idebenone [22,23], with clinical benefits particularly apparent in children and younger patients. This demonstrates the importance of early treatment instigation in these patients [23] and, in conjunction with the findings of this study, supports the case for early intervention in patients with neuroferritinopathy.…”
Section: Discussionsupporting
confidence: 62%
“…feriprone was given at the same time as idebenone, which is known to ameliorate the neurological effects of FA (29). Therefore, further studies with chelators alone in FA patients are essential.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, idebenone consistently improved cardiac hypertrophy, which is an important feature of FRDA. Neurological symptoms have not been improved as much as cardiac problems, however higher doses of idebenone especially in younger patients seem to be much more promising for neurological efficacy [76,[85][86][87].…”
Section: Idebenonementioning
confidence: 99%